Kepemilikan Insitusional sebagai Pemoderasi Pengaruh Manajemen Laba dan Perencanaan Pajak pada Nilai Perusahaan - Henock Budi Setiawan Setiawan; Lodovicus Lasdi (Yos Soedarso Economic Journal (YEJ), 2024)
This study aims to examine and obtain empirical evidence regarding the effect of earnings management and tax planning on firm value with share ownership as a moderating variable. The population and this study are non-financial companies listed on the Indonesia Stock Exchange during 2017 – 2021. The sample selection used a purposive sampling method. The company objects used in this study are 591 non-financial companies. Moderated Regression Analysis (MRA) is the data analysis method using Statistical Program for Social Science or SPSS version 20 tools. The results showed that the earnings management variable had a significant positive effect on firm value. Tax planning has a significant positive effect on firm value. institutional ownership cannot weaken the negative effect of earnings management on firm value. Meanwhile, institutional ownership can strengthen the positive influence of tax planning on firm value. Future researchers are also expected to be able to add years of research over a longer period of time in order to provide more valid results or results that are closer to actual conditions.